Adjoint-state surface wave traveltime tomography: theoretical development and applications - Hao, Shijie (Nanyang Technological University, 2025)
Surface wave traveltime tomography is a routine technique for investigating crustal and upper mantle structure. The key step in inversion is the forward modeling of traveltime using a shear wave velocity and azimuthal anisotropy model. An efficient method to conduct forward modeling is to separate it into two steps: first, model a phase velocity map from the body wave velocity model; second, model the phase traveltime between sources and receivers. In previous studies, the second step is usually conducted based on assumptions about surface wave propagation, such as assuming surface waves propagate along the great circle path between the source and receiver or using the propagation path in an isotropic velocity model for the inversion of an anisotropic model. In addition, the effects of topographic variation are also often ignored. These simplifications are not always reasonable, especially in complex media, and can lead to unreliable features in the tomographic model.